Evaluation of levels of serum immunoglobulins, proteins and the performance of Holstein heifers - Pauletti, Patricia; Neto, Raul Machado; Packer, Irineu Umberto; Bessi, Rosana (Pesquisa Agropecuaria Brasileira, 2002)
The serum immunoglobulin concentration, the total protein and the performance were evaluated in fifty-nine female Holstein heifers from birth to sixty days of life. Data were analyzed as a randomized split-plot statistical model. The animals were separated into three groups according to the initial level of passive immunity, and allocated to the groups described as follows: group 1: animals with low level of passive immunity (bellow 20 mg of IgG/mL); group 2: animals with medium level of passive immunity (between 20 and 30 mg of IgG/mL) and group 3: animals with high level of passive immunity (above 30 mg of IgG/mL). Peaks of concentration of total protein in all experimental groups were observed in the first days of live, consequence of serum immunoglobulin G of exogenous origin. No effect of the anabolism mechanism – established in the group with low level of acquired passive immunity (7.70±1.45 mg/mL of IgG) – nor of the immunoglobulin catabolism mechanism – established in the group with high level of acquired passive immunity (39.62±1.68 mg/mL of IgG) – was observed on the heifers performance on the first 60 days of life.